2021
DOI: 10.21037/apm-21-1102
|View full text |Cite
|
Sign up to set email alerts
|

Association between thyroid hormone levels and frailty in an older inpatient cohort: a cross-sectional study

Abstract: Background: Frailty is a common biological syndrome in elderly people, and the aging process regulates thyroid function. The present study aimed to determine the prevalence of frailty in an older inpatient cohort using the FRAIL scale and to evaluate the association of frailty with thyroid hormone levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…We observed that TSH levels were correlated with prevalent frailty and fatigue. Our result was thus in agreement with others that a higher TSH concentration was associated with frailty in both male and female patients [19,27,28] . The possible explanation of the role of TSH on frailty is that high TSH levels may contribute to overt and subclinical hypothyroidism, all of which may precipitate the development of overall metabolic reduction, cardiovascular decompensation, and neuromuscular abnormalities [29–32] .…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…We observed that TSH levels were correlated with prevalent frailty and fatigue. Our result was thus in agreement with others that a higher TSH concentration was associated with frailty in both male and female patients [19,27,28] . The possible explanation of the role of TSH on frailty is that high TSH levels may contribute to overt and subclinical hypothyroidism, all of which may precipitate the development of overall metabolic reduction, cardiovascular decompensation, and neuromuscular abnormalities [29–32] .…”
Section: Discussionsupporting
confidence: 93%
“…Frailty is regarded as the manifestation of aging and showed great heterogeneity as well. [2,19] Therefore, comprehensively evaluating the thyroid status and exploring the relationship between thyroid hormone concentrations and frailty among the oldest-old might help uncover the intricate pathogenesis of aging. Therefore, our study investigated the correlation between each thyroid hormone with frailty diagnosed by FRAIL scale among a group of communitydwelling oldest-old.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations